Exploring User Understanding of Advanced Driver Assistance Systems Iconography Using Novel Survey Methods. Issue 3 (March 2022) - Landry, Steven; Seppelt, Bobbie; Russo, Luca; Krampell, Martin
As advanced driver assistance systems (ADAS) increase in functionality, so do the functional requirements of their visual displays to communicate status and settings. Drivers who misinterpret in-vehicle displays may be more likely to misuse or avoid using ADAS, negating the potential safety benefits. A novel evaluation method is proposed and applied to the (at the time of surveying) latest Volvo instrument cluster. An online survey was completed by 838 Volvo car owners with varying levels of familiarity with adaptive cruise control and pilot assist. Results suggest that the concepts of a system being "available but not on" or "on but not actively providing support" can be difficult for novice users to recognize, resulting in a mode or state confusion. However, more experienced users were less likely to make these types of errors. The assessment method of providing users with partially masked images shows promise as a useful tool for evaluating comprehension of ADAS in-vehicle visual displays.